PENGARUH KEPUASAN KERJA, KOMITMEN ORGANISASI, KOMPETENSI DAN KECERDASAN EMOSIONAL TERHADAP KINERJA PEMERIKSA PAJAK DENGAN KONFLIK PERAN SEBAGAI VARIABEL MODERASI - Rilian Pratama; Vince Ratnawati; Nasrizal Nasrizal (Program Studi Pendidikan Ekonomi Universitas Riau, 2020)
This study has several objectives, first to analyze the effect of job satisfaction on theperformance of tax auditors, second, analyze the influence of organizationalcommitment on the performance of tax auditors, third, analyze the effect ofcompetency on tax audit performance, fourth, analyze the influence of emotionalintelligence on tax audit , to analyze the effect of job satisfaction, organizationalcommitment, competence, emotional intelligence on the performance of tax auditorsafter being moderated by role conflict. Role conflicts are expected to have aninfluence on the performance of tax auditors. The population of this research is 139tax examiners in the Riau Regional Directorate General's Regional Officeenvironment as many as 139 people and the sampling method is saturated samples.Data processed is primary data obtained by processing questionnaire data. Datawere analyzed with the help of the Smart PLS Version 3.2.8 program. The results ofthe study prove that job satisfaction does not affect the performance of the taxexaminer and organizational commitment, competence and emotional intelligencepositively significantly affect the performance of tax examiners. While that roleconflict does not moderate the relationship between job satisfaction, organizationalcommitment, competence and emotional intelligence to the performance of taxauditors.